Editorial - Tsallis, Alexandra Cleopatre; Mattos, Amana; Jacó Vilela, Ana Maria; Mendes, Deise Maria Fernandes; Quadros, Laura Cristina de Toledo; Darriba, Vinicius Anciães (Estudos e Pesquisas em Psicologia, 2019)
Alexandra Cleopatre Tsallis, Amana Mattos, Ana Maria Jacó Vilela, Deise Maria Fernandes Mendes, Laura Cristina de Toledo Quadros, Vinicius Anciães Darriba